Negosiasi Pemuda dalam Fleksibilitas Pasar Kerja: Studi Netnografi terhadap Mikro-Selebriti di Daerah Istimewa Yogyakarta - Arif Budi Darmawan; Faishal Abdul Azis; Mei Nurul Aini (Universitas Gadjah Mada, 2019)
Today the labor market flexibility to be a trend among young people. This emergence of flexibility becomes an ambivalence. On the one hand, it is a form of adaptation with increasingly mobile work. However, according to Guy Standing flexibility actually produces new dangerous class. The vulnerability arises in the form of no guarantee of protection for workers and the security of the labor market. Through netnographic studies the author seeks to examine the employment choices of youth as micro-celebrities, the benefits gained, obstacles faced and negotiations carried out to answer the uncertainty that leads to his work. The researcher observed through the internet and conducted in-depth interviews. The selection of research informants was purposively conducted, namely, micro-Sebritic workers living in the Special Region of Yogyakarta in ages 16-30 years. From the results of the study found that: First, working as a micro-celebrity is the need for leisure. For young people working as micro-celebrities is a hobby as well as a profession. Second, many micro-celebrities are faced with dilemmas and uncertainty situations, both coming from themselves and parents. Finally, negotiations are carried out by youth to deal with uncertainty over their work and the dilemma they face.